2015
DOI: 10.1016/j.jvs.2014.11.079
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum cystatin C level is an independent predictor of contrast-induced nephropathy and adverse outcomes in patients with peripheral artery disease undergoing endovascular therapy

Abstract: We found elevated baseline cystatin C level to be an independent risk factor for CIN and a predictor of all-cause mortality and major adverse events in patients with PAD undergoing endovascular therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
2
19
0
1
Order By: Relevance
“…In all these investigations the peak of serum CysC was significantly associated with the development of CIN occurring 24-48 hours after PCIP. Moreover, in agreement with previous studies (12,19,20), our investigation demonstrated that high baseline values of CysC are associated with CIN occurrence.…”
Section: Discussionsupporting
confidence: 93%
“…In all these investigations the peak of serum CysC was significantly associated with the development of CIN occurring 24-48 hours after PCIP. Moreover, in agreement with previous studies (12,19,20), our investigation demonstrated that high baseline values of CysC are associated with CIN occurrence.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, over 40% of patients were excluded in the BCBS analysis due to missing serum creatinine levels postintervention—and therefore cases of AKI may have not been captured. Of note, the present mean incidence of 10.4% is also comparable to smaller studies that included a significant proportion of CLI patients …”
Section: Discussionsupporting
confidence: 85%
“…After removal of duplicates and nonrelevant articles, 50 potentially relevant studies were identified and ultimately 20 studies were selected that included data on patients undergoing peripheral angiography or interventions. These 20 studies were then analyzed in detail and separated into those with ( n = 15) (Table ) and without ( n = 5) granular data regarding lower extremity peripheral angiography related AKI incidence . The aggregate median data from the 15 studies are shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Given the rise in contrast based lower extremity angiograms, AKI in patients with PAD continues to be an important complication. Progress in this area has been hampered by variable definitions of AKI, lack of uniform measurement of serial serum creatinine levels during the days following endovascular therapy, and reliance on only serum creatinine as the sole biomarker of renal injury . Further complicating this field is the fact that the term lower extremity PAD incorporates a broad range of clinical presentations including asymptomatic disease, lifestyle limiting claudication, acute limb ischemia, and critical limb ischemia—with or without tissue loss.…”
Section: Introductionmentioning
confidence: 99%